Alphabet books: The nature of parents' shared reading between and across books. (March 2021) - Bergman Deitcher, Deborah; Aram, Dorit; Goldberg, Adva
This study examined the nature of parents' shared reading with their preschoolers between and across two different alphabet trade books. The "busy" book contains more sentences and words per page, more complex illustrations per page, and the target letter takes up less of the page and appears in the same colour as the text. The "less busy" book contains fewer sentences and words per page, simpler, more monochromatic illustrations, and the target letter takes up more of the page and appears in a different colour from the text. Participants included 46 parent–child dyads from middle SES homes. The children (13 boys, 33 girls) ranged from 4-years-old to 6.8-years-old (M = 5.63, SD = 0.6). Results revealed that parents made more references to the writing system and to more narrative elements when reading the "less busy" book. They also requested their children's responses more when reading this book. Parents made more references to the illustrations and regulation of behaviour when reading the "busy" book. These results went beyond the child's language level and the parent's education level, controlling for the overall number of utterances. Findings also showed that parents seem to have a consistent style across both alphabet books, such that the more characteristics of the shared reading appeared during one book, the more they featured in the shared reading of the other book. Parents may benefit from exposure to different types of alphabet books and how their varying characteristics can impact on discourse style.